Komunikasi Terapeutik Petugas Kesehatan Berhubungan dengan Kepuasan Pasien - Suraying, Suraying; Jufriyanto, Mohammad; Hafidah, Lailatul; Amir, Faisal; Suprayitno, Emdat (Fakultas Ilmu Kesehatan, 2025)
The lack of effective communication between health workers and patients is one of the low causes of patient satisfaction in a number of regional hospitals. The success of health workers in providing services, both physical and psychological, determining the recovery and satisfaction of patients. This study aims to examine relationships between therapeutic health workers and patient satisfaction rates. This study used a cross sectional analytic method, Data were collected using the Likert scale questionnaire and analyzed using Chi-Square test at a significance level of 0.05. The population of this research all patients who undergo treatment at RSUD dr. H. Slamet Martodirdjo which is taken based on average, a month of 414 people with a total of 207 respondents taken using purposive sampling technique. Data collection uses questionnaires. The results showed that 79.2% of respondents considered therapeutic health workers communication, and 75.8% were satisfied with the service received. From the analysis of the Chi-Square test showed p-valure 0.000 <0.05 which means H1 is accepted and Ho was denied, so it can be concluded that this outcome emphasizes the importance of therapeutic communication to improve the quality of patient services and satisfaction at DR. H. Slamet Martodirdjo hospital.